Seroprevalence of Pasteurella multocida Serotype A2 in Cattle, Afar Region, Ethiopia - Fanuel Bizuayehu Yihunie; Ashenafi Syoum; Teshager Dubie (Veterinary Medicine International)
Bovine respiratory disease (BRD), also known as shipping fever, is an economically significant disease affecting cattle in Ethiopia and is caused by the Pasteurella species. There is limited information on the serological prevalence of these species in Ethiopia. This study aimed to identify serotype A2 and estimate the seroprevalence of Pasteurella multocida in cattle in the Asayita, Dubti, and Chifra districts of Afar Region, Northeastern Ethiopia. A cross-sectional study was conducted on randomly selected cattle from November 2023 to June 2024. Blood samples were collected from nonvaccinated bovine species, recording sex, age, and body condition. Descriptive statistical analysis was used to summarize the results, with data managed using Microsoft Excel and analyzed with SPSS Version 20. Descriptive statistics were employed to determine the occurrence of the serotype. The chi-square test was employed to determine the association between variables. 93.8% of tested blood samples were found positive for Pasteurella multocida serotype A2. Among the factors tested, body condition scores showed a significant association (x2 (2, N = 384) = 34.07, p≤0.001) with the prevalence of the serotype. This study provides valuable insights into the seroprevalence and serotype distribution of Pasteurella multocida in the study area, highlighting the need for targeted control measures.